Metabolic syndrome patterns by gender in major depressive disorder. - Lu Li; Ling Xiong; Zhihua Liu; Lin Zhang (PLoS ONE)
Major depressive disorder (MDD) and metabolic syndrome (MetS) are significant health challenges, with distinct gender-specific manifestations. This suggests that the clinical presentation of MetS within the MDD cohort may also vary by gender. The objective of this study is to explore these gender-specific clinical patterns in the co-occurrence of MetS among hospitalized MDD patients, thereby offering insights and guidance for targeted interventions aimed at managing MetS in this demographic. The study included 1,281 first hospitalization MDD patients. Data were collected on socio-demographic characteristics and general clinical profiles. Metabolic parameters, routine biochemical markers, and psychological symptoms were measured and analyzed. The prevalence of MetS was 8.21% in male patients and 10.34% in female patients, with no significant difference between genders. Gender-specific risk factors were identified: in males, age and anxiety symptoms were significant predictors of MetS, while in females, age at onset and married were linked to the development of MetS. Additionally, MetS severity was influenced by age at onset in males and by both age at onset and married in females. This study found no gender-specific prevalence of MetS in hospitalized MDD patients. However, gender-specific factors influencing MetS development and severity highlight the need for focused management in older, married females and older males with high anxiety symptoms.